Meningkatkan Hasil Belajar Siswa Kelas XI IPA-1 SMA Negeri 1 Jorong Melalui Pembelajaran Kooperatif Tipe Somatic Auditory Visual And Intellectual Pada Pokok Bahasan Impuls Dan Momentum - Dewi Dewantara; M. Arifuddin Jamal; Syubhan An'nur (Berkala Ilmiah Pendidikan Fisika, 2013)
The low of student’s achievements were indicated because the students were not active and the teacher’s lack of skill. This condition needs a further research in order to improve the student’s achievement through cooperative learning type SAVI in impulse and momentum subject. The specific purposes of this research are to describe: 1) teacher’s skill, 2) the student’s achievements; 3) the students’ participation in the classroom; and 4) the students’ responses. These research were classroom action research that consists of 3 cycles. The instruments were used Lesson Plan, Worksheet, Evaluation Sheet, affective scoring sheet, teacher’s skill and student’s participation observation sheet, and the students’ response observation sheet. The data were acquired by the observation results, questionnaire, and documentation. The results of this research were: 1) The teacher’s skill was improved from 99.21% to 96% and 99.28%; 2) the students’ achievements including cognitive and affective aspects were improved from 81.46% to 88.1%, and 90.96%; 3) The participation of students in teaching and learning process were also increased from 63.67% to 84.43%, and 85.5% in cycle III, 4) the students’ responses during teaching and learning process were very good. According to the results, it can be concluded that the achievements of XI IPA-1 students of SMA Negeri 1 Jorong in learning impulse and momentum were improved after the treatment of cooperative learning model type SAVI.